Pengaruh Kultur Teknis terhadap Serangan Hama Spodoptera litura pada Tanaman Cabai Merah (Capsicum annuum L.) di Desa Kerinjing Kecamatan Dempo Utara Kota Pagar Alam Provinsi Sumatera Selatan: Effects of Cultural Technique on The Infestation of Spodoptera litura on Red Chilli (Capsicum annuum L.) Cultivation In Village Kerinjing, District Dempo Utara City of Pagar Alam, South Sumatra - Arsi Arsi; Ahmad Kemal (Politeknik Negeri Lampung, 2021)
ABSTRACT Red chilli (Capsicum annuum L.) is a vegetable crop belongs to Family Solanaceae. The high daily demand of the commodit have made the crop become strategic commodity. In the cultivation of red chilli, there are some obstacles faced by the chilli farmers. The main obstacle is disturbance by pests and diseases. The damages caused by pest had reduced the crop yield because the crop cannot growth and development optimally. The objective of this field study was to know the effect of cultural technique on pest species, population and damage caused by the pest on red chilli (Capsicum annuum L.) in Village Kerinjing District Dempo Utara, City of Pagar Alam, South Sumatra. Observation method included sample land determination, sample plot determination, and sample plants determination, also observing pest population and damage intensity caused by the pest. Observation was conducted in 3 red chilli cultivations of different ages. Pest population and damage intensity were analysed using analysis of variance with 5% degree of significant. Pest found in red chilli cultivation was Spodoptera litura (Lepidoptera: Noctuidae). Based on field observation, the difference in cultural technique among the chilli cultivation sampled had significant effect on pest population and damage intensity caused by Spodoptera litura. Keywords: Red chilli crop, cultural technique, pest.